Life in the doghouse [videorecording (DVD)] - Davis, Ron (Documentary filmmaker); Davis, Ron (Documentary filmmaker); Danta, Ron; Robershaw, Danny ([publisher not identified], 2019)
The story of Danny & Ron's Rescue, an organization formed by Danny Robershaw & Ron Danta which has been providing care for dogs in need since 2005.